Scale of employees’ initiative for proactive health: development and validity testing - Qianqian Huang; Feng Jiang; Huanzhong Liu; Lufa Zhang; Yi-Lang Tang (BMC Psychology)
Abstract Background Non-communicable diseases (NCDs) pose a significant public health challenge, with employees particularly vulnerable due to modifiable lifestyle risk factors. Proactive health underscores the importance of self-initiated behaviors in disease prevention and health promotion. However, existing measures primarily assess workplace initiative, overlooking its relevance to health. This study aims to develop and validate the Employees’ Initiative for Proactive Health (EIPH) scale to address this gap. Methods The instrument development phase identified 11 preliminary items through literature review and expert consultation with five experts. The item discrimination index, item-total correlations, preliminary reliability, and exploratory factor analysis (EFA) were performed on a pilot sample of 204 participants, followed by confirmatory factor analysis (CFA) and concurrent validity on the main sample of 289 participants. The cutoff value was also assessed. Results The EIPH scale was refined to five items, with eigenvalues greater than 1, accounting for 45.71% of the variance. Standardized factor loadings for the CFA indices ranged between 0.41 and 0.55. The correlation coefficient for concurrent validity was 0.569 (p < 0.001), and Cronbach’s α coefficient for reliability was 0.58. The cutoff value was 18.5 points. Conclusions The scale demonstrated reasonable and reliable measurement of EIPH among Chinese participants.